The Use of Structural Concrete with the Addition of Non-Metallic Fibers in Civil Construction, a Technological Prospect - Discher, Marcos Gottschalg (2023)
The addition of fibers in concrete has been proving to be an effective tool for improving the performance and durability of structural elements in buildings. The objective of this work was to carry out a study on the use of non-metallic fibers in concrete, identifying the most used types and areas of application. For this, technological prospection was carried out through exploratory research with a quantitative and qualitative approach, based on the results of scientific publications by CAPES and Web of Science, and patents by INPI and Orbit. The survey pointed to a growth in the study of the subject in the last ten years, with a leadership in the use of synthetic fibers, followed by polymeric fibers and thirdly by vegetable fibers, and concrete with the addition of fibers has been used mainly in areas where environmental aggressiveness, abrasion and tensile stresses are crucial for structural stability.